Artifactual Communication Activities of the transfer of the 10th Century Mahendradatta Women’s Historical Women’s History - Ratnawulan, Nina Septiana; Prahasti, Gyan; Pelagia, Merli (Jayapangus Press, 2023)
One of the most important needs besides food and shelter is clothing, a primary human need. The purpose of this study is to determine the audience's acceptance of the transfer of the history of women in the 10th century AD in the figure of Mahendradatta in the hertorianke style in artifactual communication activities and its communication applications in transferring the history of women in the 10th century AD with the figure of Mahendradatta to fashion brands carried out. This research belongs to the type of qualitative research. In this study, the technique used to select informants. The result of the research is the meaning of the Herstori fashion brand in artifactual communication activities as a vehicle for women's history in the 10th century AD. With the presence of Herstori, Mahendradatta is adequate. The change of vehicle that occurred in the fashion-themed